E.W. Rector, Digest of the Laws and Ordinances of the City of Hot Springs, with the Constitution of the State of Arkansas, General Incorporation Laws of the State and Amendments Thereto 61, § 131 (1887) - (:unkn) unknown (My University, 1886)
Prohibited the carry of gun powder, giant powder, dynamite, nitro-glycerine or blasting powder on any vehicle in any part of the city unless secured in kegs, boxes, or canisters capable of preventing leakage of the materials and covered in sheets of canvas or other clothes
Keywords: GUNPOWDER - TRANSPORTATION